Some reflections on a word formation in teaching German as a foreign language - Mac, Agnieszka (Glottodidactica, 2009)
The goal of this article is to expatiate on the important function of the morphological structures in foreign language teaching. Firstly, I will try to answer the question about morphology’s position in foreign language teaching. Furthermore, I will focus on the difficulties arising with implementing teaching methods of word formation rules. The third part deals with the effects of morphology in the didactical field with regard to teaching German as a foreign language.